TRANSFORMASI DIGITAL PERPAJAKAN: STRATEGI UMKM DI BOGOR UNTUK MEMPERKUAT KEPATUHAN DAN DAYA SAING MELALUI PELATIHAN DAN PENDAMPINGAN - Dwianika, Agustine; Kurniawan, Budi; Said, Lina; Herianti, Eva; Marundha, Amor; Fernando, Kenny; Widiastuti, Ni Putu Eka (Universitas Trisakti, 2025)
This Community Service (PKM) program aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Curug Village, Bogor Regency, in understanding and utilizing digital-based taxation services. The activity, organized by the Forum of Accounting Lecturers of Higher Education (FDAPT) of the Indonesian Accountants Association, Jakarta Region, focuses on training and mentoring regarding e-SPT, MSME taxation, tax rates, and tax calculations, as well as promoting digital adoption in financial administration. A participatory and applied approach was used, involving partner needs identification, intensive training, and continuous mentoring. Evaluation was conducted through a comparison of pre-test and post-test scores. Results show a significant increase in participants' knowledge regarding digital tax obligations, with 85% of participants able to perform e-Filing and e-Billing independently and 70% beginning to use simple financial recording applications. A paradigm shift occurred from